The Impact of Declining Oil Rents on Tax Revenues: Does the Shadow Economy Matter? - Phoebe W. Ishak; Mohammad Reza Farzanegan (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the association between oil rents and tax revenues, highlighting the importance of the shadow economy as a mediating factor. We present a simple theoretical model demonstrating that decreasing oil rents are likely to be positively associated with the tax revenues in a country with a moderate size of shadow economy. Declining oil rents may not lead to higher tax efforts of the state if the shadow economy is sizable. Using a sample of 124 countries from 1991 to 2015, our panel data regression analysis illustrates the moderating role of the shadow economy in the final effect of negative oil rents shocks on the tax revenues. A decline in oil rents following negative oil price shocks cease to have any significant positive impact on tax revenues in countries with shadow economy representing more than 35% of GDP. The results are robust after controlling country and year fixed effects, other determinants of tax revenues and using a dynamic model.
Keywords: Q32; Q35; H26; O17; 330; shadow economy; tax revenues; oil rents; resource curse